Kekuatan Penempelan Bysus Kerang Hijau (Perna viridis) Pada Media Penempel - Yonvitner Yonvitner (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2010)
Green mussel is a mollusk class that has been developing to culture system.  The perna viridis culture using bagan with rope as settling media.  Settlement of perna on rope that strongly will support the survival rate of mussel.  This research done to assessing bysus on rope media in water column.   Sampel take from culturing area in Muara Kamal station.  The Measurement of bysus strength use Shimadzu Autograp AGS-D Series.  Data collected analyzed are descriptive and  principal component  analyses.  Water quality that measure are temperature (30,1 oC), current (0,115 m/dt), Salinity (28,89 promil).  Bysus elongasi strength between 4,598-7,892 with bysus line reach 20-60 piece.  Break point  yarn much happen at plaque site from bysus.